La educación ambiental en el proceso de enseñanza aprendizaje en el primer año de bachillerato general unificado de la Unidad Educativa " Carlos Bayardo Limaico Bassante" durante el año lectivo 2018-2019. - Sacatoro Toaquiza, José Ignacio (2020)
The research called "Environmental education in the teaching-learning process in the first year of the Unified General Baccalaureate of the educational unit" Carlos Bayardo Limaico Bassante "during the 2018-2019 school year" aims to raise awareness of environmental care as an essential component in the teaching-learning process. The lack of knowledge about the problem of environmental protection has caused the deterioration of the natural environment, in order to solve the problem identified, the main objective is to strengthen environmental education in students in the first year of high school through the implementation of strategies of conservation and environmental awareness, in order to comply with the proposal, the qualitative methodology was used from an induction approach, to obtain the information was supported by observation techniques, surveys and interviews; the results reflected that there is very little environmental culture and for which there is total appropriation of their school and natural environment. All these inputs have been used to prepare the proposal entitled Program of Good Environmental Practices, whose results in its application were satisfactory because it allowed improving and developing skills in each member of the educational community to contribute to the correct application of the different good activities environmental practices